ECONOMIC EFFECTS OF THE THERMAL WATER USE IN VEGETABLE PRODUCTION ON THE TERRITORY OF CENTRAL DANUBE REGION - Subić, Jonel; Nastić, Lana; Potrebić, Velibor (Economics of Agriculture, 2013)
Investments in agricultural production due to modernization of production process, is one of the basic factors for agriculture and rural areas development generally, as well as the entire economy. In the existing business conditions, when domestic agriculture meets alarming problems in primary production sphere (as: work productivity, insufficient number of work places, low efficiency of instruments of labour etc.), increase of investments size can significantly affect competitiveness improvement, as on domestic, as well as on foreign market. The investment in building the exploitation wells, out of which will get thermal water, which will serve for irrigation and heating of a glasshouse for production of early and late vegetables out of a season, represents the significant modernization of agricultural production. Such form of investment can be a good example, aiming to improve the production process and increase of income on a family agricultural husbandry.